Sincronia e índice de divergência de diversidade de espécies anemocóricas - Massi, Klécia Gili (2006)
The Cerrado Domain is the second largest Brazilian phytogeographic province, occupying originally 23% of Brazil s land surface, under seasonal climate. The cerrado presents a floristic and physiognomic variation, ranging from grassland to tall woodland. Anemochorous species are proportionally more important in the cerrado than in Brazilian rain forests, especially in open physiognomies. Morphological designs of wind-dispersed diaspores appear to slow their rates of descent, increasing their chances of exposure to winds and of reaching safe sites to germinate. Wind-dispersed species are constrained to fruit during the best time for seed dispersal. Also, the height of seed release and surrounding vegetation are fundamental to long-distance dispersal. We selected the wind-dispersed species from three phytosociological surveys (disjoint and core sites) and classified them into autogyro, rollingautogyro, floater, or undulator, according to the diaspore morphology and aerodynamic behavior in still air. For each species, we had data on its fruiting period. We tried to assess whether there was a seasonality and, if there was, whether it was synchronized with some climatic conditions. The number of fruiting anemochorous cerrado species was highest at the dry season, coinciding with reduced precipitation. Next, we studied the anemochorous diaspore spectra and index of divergence from species to anemochorous diaspore diversity (IDD) in three cerrado physiognomies (campo cerrado, cerrado sensu stricto, and cerradão) in a disjoint site and three cerrado physiognomies (cerrado sensu stricto) in different floristic pronvinces. There was a floristic unit among the cerrado physiognomies, with the ecotonal ones containing both grassland and woodland elements. Both nuclear and disjoint sites were ecologically similar regarding the species distribution. However, there were differences when species abundances were considered. In denser sites, vegetation reduces wind velocity in ...